Role of Educational Institutions in Combating Hoax News: The Qur'an Perspective - Hana Nadia; Muhammad Fazlurrahman Hadi (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2020)
The rapid development of the times and sophisticated technology create a limitless space that ultimately leads to a variety of positive and negative impacts, the positive impact is very easy to get information, while the negative side is a lot of information that can not be answered so that a lot of lies spread. This type of research is library research, namely research whose main object is books or other sources of literature. That is, data are sought and found through literature reviews from books that are relevant to the discussion. Educational institutions have a great responsibility in shaping the ethics and personality of their students. The Qur'an as a source of scientific excavation has offered concepts to humans, especially student education through learning materials for Islamic religious education. The results build on formulations on how to build personalities for honest students and avoid the lies of Islamic educational institutions. Keywords: Education, Hoax News, Qur'an